On normal and strongly normal lattices - El-Bachir Yallaoui (International Journal of Mathematics and Mathematical Sciences)
In this paper we will investigate the properties of normality and strong normality of lattices and their relationships to zero-one measures. We will eventually establish necessary and sufficient conditions for lattices to be strongly normal. These properties are then investigated in the case of separated lattices.